American folklore and legend - Reader's Digest Association (Pleasantville, N.Y. : Reader's Digest Association, 1978)
An anthology of popular American stories, poems, songs, and lore that have become part of the folklore of the United States.
At head of title: Reader's digest.
Includes bibliographical references and index.
Keywords: United States -- Social life and customs; Folklore; Legends